2019
DOI: 10.5152/ejbh.2019.4848
|View full text |Cite
|
Sign up to set email alerts
|

Lymph Node Ratio (LNR): Predicting Prognosis after Neoadjuvant Chemotherapy (NAC) in Breast Cancer Patients

Abstract: European Journal of Breast Health (Eur J Breast Health) is an international, scientific, open access periodical published by independent, unbiased, and double-blinded peer-review principles. It is the official publication of the Turkish Federation of Breast Diseases Societies, and Senologic International Society is the official supporter of the journal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 32 publications
2
15
0
Order By: Relevance
“…25 In addition, another similar study, where TNBC accounted for 20.5%, reported a significant association between ypN +, OS, and DFS in the Cox regression. 26 However, when both ypN and LNR were included in the model, the LNR has a greater impact on DFS and OS [27][28][29][30] ; other studies reported that LNR was the only independent prognostic factor. 14,31 In our adjusted model, we found that the effect of ypN staging became nonsignificant.…”
Section: Discussionmentioning
confidence: 99%
“…25 In addition, another similar study, where TNBC accounted for 20.5%, reported a significant association between ypN +, OS, and DFS in the Cox regression. 26 However, when both ypN and LNR were included in the model, the LNR has a greater impact on DFS and OS [27][28][29][30] ; other studies reported that LNR was the only independent prognostic factor. 14,31 In our adjusted model, we found that the effect of ypN staging became nonsignificant.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have proven that the LNR may serve as a better predictor of survival in patients with CRC because it is less affected by the total number of retrieved nodes [ 10 , 12 14 ]. Therefore, as an alternative or complementary method, LNR have been suggested for AJCC staging [ 15 ]. It aims to improve the prognosis for CRC by reducing the effect of heterogeneity of procedures on staging lymph nodes.…”
Section: Introductionmentioning
confidence: 99%
“…A bootstrap regression study from Geneva, Switzerland, introduced the 0.20, 0.65 cutoffs 21 . Numerous other studies have confirmed the superiority of the lymph node ratio and the cutoffs; we cite non exhaustively from the US, Korea, Netherlands, Italy, China, Turkey, in diverse conditions such as triple negative breast cancer 22 – 28 . There is neither anything new in the RMST.…”
Section: Discussionmentioning
confidence: 99%